Analysis of sharia accounting implementation in BMT (Baitul Maal wat Tamwil) Alif Yogyakarta / Asri Noer Rahmi - Asri Noer Rahmi (UiTM Cawangan Johor, 2020)
This study aims to analyse the implementation of Sharia Accounting at BMT Alif Yogyakarta. From the financial reporting presented by BMT Alif, it can be seen the financial reporting system used and applied by BMT Alif Yogyakarta. Is it in accordance with the application of Sharia accounting in Indonesia and guided by PSAK (guidelines for financial accounting standards) 101 issued by the Indonesian Experts Accountants (IAI). This study used a comparative descriptive research methodology, which is a quantitative method in the form of numbers obtained from the financial statements presented and qualitative methods based on the results of the financial section interview at BMT Alif Yogyakarta. The findings indicated that BMT Alif Yogyakarta understands the standards of Sharia accounting applications in Indonesia and has implemented sharia accounting financial statement, this can be seen from the implementation of financial reporting and also appropriate financial reporting standards, in accordance with applicable SFAS 101. This can be seen from the financial reporting presented. Financial statements are in the form of balance sheets, income statements, cash flow statements, retained earnings reports (equity), reports on changes in limited investments, and the separation of reports on sources and uses of zakat funds and social funds, reports on sources and uses of qardh funds and notes to financial statements.